Two-liquid urethane molding material for optical lenses and optical lens made of polyurethane resin

JP2023126778A5Pending Publication Date: 2025-01-20TALEX OPTICAL
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2023095388
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-06-09
Publication Date
2025-01-20

AI Technical Summary

Technical Problem

Existing polyurethane resin molding materials for optical lenses, particularly those using 4,4'-methylenebis(2-chloroaniline) (MOCA) as a curing agent, suffer from thermal discoloration issues that affect transparency and color stability, posing health hazards and reducing production efficiency.

Method used

A two-component urethane molding material composed of an isocyanate-terminated prepolymer derived from alicyclic diisocyanate and polyhydroxy compound, combined with dimethylthiotoluenediamine (DMTDA) or diethyltoluenediamine (DETDA) as a curing agent, which allows for uniform mixing at low temperatures, preventing thermal deterioration and maintaining transparency and color stability.

Benefits of technology

The material ensures high transparency and stable color tone in optical lenses, enabling efficient production of lenses with polarizing properties without yellowing or brown discoloration, improving manufacturing efficiency and safety.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000011_0000
    Figure 00000011_0000
  • Figure 00000011_0001
    Figure 00000011_0001
  • Figure 00000011_0002
    Figure 00000011_0002
Patent Text Reader

Abstract

To obtain a method for manufacturing a polarizing lens for eyeglasses, in which an optical lens composed mainly of polyurethane resin does not exhibit yellow or brown coloring due to the thermal degradation of a curing agent and maintains high clarity and stability after manufacturing, and can be molded by casting at as much low temperature as possible.SOLUTION: Provided is a method for manufacturing a polarizing lens for eyeglasses, using a two-liquid urethane molding material for optical lenses comprising a main agent that includes an isocyanate-terminated prepolymer which is an intermediate product of the polyurethane generation reaction of an alicyclic diisocyanate and a polyhydroxy compound, and a curing agent that includes dimethylthiotoluenediamine (DMTDA) or diethyltoluenediamine (DETDA) or an aromatic diamine as a mixture of these.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a two-component urethane molding material for optical lenses, which is a molding material for optical lenses such as lenses having polarization properties, a polyurethane resin optical lens which is a molded body thereof, and a method for manufacturing a polyurethane resin optical lens.

Background Art

[0002] Generally, as a molding material for optical lenses, a two-component mixed type polyurethane resin molding material for optical lenses is known, in which a main agent mainly composed of an isocyanate-terminated prepolymer obtained by reacting an alicyclic diisocyanate and a polyol and a curing agent mainly composed of an aromatic polyamine are mixed and reacted (Patent Document 1).

[0003] The aromatic polyamine of the above-mentioned curing agent consists of 4,4'-methylenebis(2-chloroaniline) [or 3,3'-dichloro-4,4'-diaminodiphenylmethane], and what is abbreviated as MOCA is well-known.

[0004] However, when manufacturing an optical lens made of polyurethane resin using MOCA as a curing agent, there is room for improvement of the curing agent because the optical lens may turn yellow after heating during molding. That is, the polyurethane resin molding material composition for optical lenses using MOCA as a curing agent shows a light yellow color when melted and is likely to change to brown over time. Therefore, it has been difficult to stably maintain the transparency and color tone of the manufactured optical lenses over time.

[0005] In particular, in optical lenses with high transmittance or vivid color tones, the discoloration of MOCA is likely to be conspicuous, thereby reducing the transmittance of the optical lens and also reducing the vividness of the original color tone.

[0006] To predict the degree of discoloration over time and perform color correction (bluing) requires advanced knowledge and experience regarding pigments and dyes, such as selecting the appropriate pigment for color correction and adding the correct amount to the material (prepolymer) before molding and curing. Therefore, when such color correction work is necessary, production efficiency decreases.

[0007] Regarding improvements to polyurethane for optical lenses, a technique is known in which 4,4'-methylenebis(2-chloroaniline) purified to have a Gardner color number of 2 or less is used as a curing agent for optical lenses requiring light color or uncolored transparency, and an antioxidant is further added to suppress yellowing (the curing agent is also called white mocha) (Patent Document 2).

[0008] The curing agent (MOCA) mentioned above is a chlorine-containing compound and is also carcinogenic. However, if it is added in a necessary and sufficient amount for the molecular chain extension reaction and the curing reaction is completed, it will not remain in the product. However, since it is necessary to prevent health hazards to occupational safety and health during the manufacturing process of polyurethane resin products, measures to ensure safety during the work process are required, for example, when it is necessary to cure a large amount of polyurethane resin in the atmosphere at once.

[0009] In technological fields other than optical lenses, two-component urethane curing agents are used as substitutes for MOCA for safety reasons, and diethyltoluenediamine (hereinafter sometimes abbreviated as DETDA) is a known curing agent.

[0010] This curing agent is a two-component urethane waterproofing material composition comprising a main component containing an isocyanate-terminated prepolymer made of tolylene diisocyanate and polyol, which is used as a waterproofing material applied to the rooftops of buildings, and a curing agent. It is known that diethyltoluenediamine (hereinafter sometimes abbreviated as DETDA) is used as the curing agent (Patent Document 3).

[0011] Furthermore, a two-component urethane paving material is known for providing elasticity to the surfaces of stadiums, grounds, racetracks, etc., and contains 90% or more by mass of dimethylthiotoluenediamine (DMTDA) as a hardening agent (Patent Document 4). [Prior art documents] [Patent Documents]

[0012] [Patent Document 1] Japanese Patent Publication No. 2002-187931 [Patent Document 2] Japanese Patent Publication No. 2003-301025 [Patent Document 3] Japanese Patent Publication No. 2015-21021 [Patent Document 4] Patent No. 64422638 [Overview of the Initiative] [Problems that the invention aims to solve]

[0013] However, the two-component urethane paving materials and waterproofing materials described in Patent Document 3 or Patent Document 4 above do not give much consideration to transparency or color tone, meaning they are used in applications where optical properties are not required, or, since waterproofing materials and road paving materials do not need to have a high level of molten fluidity to enable casting, they are not materials that have a long pot life in a low viscosity state that is suitable for casting.

[0014] On the other hand, molding materials for optical lenses, such as eyeglass lenses, need to have a long pot life in a low viscosity state that allows for casting. Furthermore, dyes may be added to adjust the transmittance in the visible light range or other infrared and ultraviolet ranges, or to enhance contrast, and if polarization is required, the addition of necessary dyes or compounding with films containing such dyes is also necessary. Therefore, it is necessary to minimize thermal degradation of the dyes, and the material must have low-temperature melting fluidity so that it can be molded at the lowest possible temperature.

[0015] Therefore, the objective of this invention is to provide a two-component polyurethane molding material for optical lenses that is mainly composed of polyurethane resin and can be cast, so that it does not turn yellow or brown due to thermal degradation of the curing agent, and so that the dyes added to the optical lenses do not undergo thermal denaturation, and so that it can be cast at the lowest possible temperature. Furthermore, the objective is to provide a two-component polyurethane molding material for optical lenses that can produce optical lenses of stable quality without changing the transparency or color tone of each optical lens, even if the molding material has undergone mixing, molding, and curing processes, even if the lens has polarizing properties due to a polarizing film, a lens with high transmittance that is easily affected by color, or a lens with a vivid color tone.

[0016] Another objective of this invention is to create polyurethane resin optical lenses made from cast molded articles that maintain stable quality without changes in color or transparency over time, using such a two-component polyurethane molding material for optical lenses, and to efficiently manufacture such high-quality polyurethane resin optical lenses. [Means for solving the problem]

[0017] To solve the above problems, this invention provides a two-component urethane molding material for optical lenses, comprising a main component containing an isocyanate-terminated prepolymer, which is an intermediate product of the polyurethane formation reaction between an alicyclic diisocyanate and a polyhydroxy compound, and a curing agent containing an aromatic diamine that is liquid at room temperature, wherein the aromatic diamine is dimethylthiotoluenediamine (DMTDA), diethyltoluenediamine (DETDA), or a mixture thereof.

[0018] As described above, the two-component urethane molding material for optical lenses of this invention has an isocyanate-terminated prepolymer as the main component, which is an intermediate product of the polyurethane formation reaction between an alicyclic diisocyanate and a polyhydroxy compound, and a predetermined aromatic diamine that is liquid at room temperature. Because these can be mixed uniformly with minimal viscosity differences under relatively low mixing conditions of 100°C or below, the curing reaction can be carried out with good curing efficiency and uniformity, without generating foreign matter containing unreacted curing agent, and the polyurethane resin optical lens made from the cast molded product can maintain a stable state of high transparency over time.

[0019] Furthermore, by using the aforementioned specified main agent and hardener, the pot life necessary for casting optical lenses is obtained, improving the workability of casting the lenses. In addition, polarized lenses equipped with a polarizing film, lenses that are susceptible to coloration and have high transmittance, or lenses with vivid colors become high-quality optical lenses with stable color over time.

[0020] The mixing ratio of the curing agent is preferably 4 to 37 parts by mass per 100 parts by mass of the main component, so that lenses requiring light color or uncolored transparency can be molded with good workability and for the required pot life.

[0021] Furthermore, since the curing agent is a mixture of 15 to 25 parts by mass of dimethylthiotoluenediamine and 1 to 10 parts by mass of diethyltoluenediamine per 100 parts by mass of isocyanate-terminated prepolymer contained in the main component, it becomes easier to adjust the pot life required for casting. By speeding up the curing time as much as possible, thermal degradation of the appropriately blended pigment components can be reduced, stably improving the performance and quality of the color tone and pigments, and also improving production efficiency.

[0022] The optical lens in which the above-described effects are remarkable is preferably a lens having polarization property provided with a polarizing film integrally, and more preferably the lens having polarization property is an eyeglass lens having a high transmittance of 30 to 90% in the visible light range.

[0023] When the above-described two-component urethane molding material for an optical lens is used, a polyurethane resin optical lens made of a cast molded body with a stable quality and no change in color tone over time can be obtained.

[0024] In order to efficiently manufacture an optical lens having the above-described effects, for example, an alicyclic diisocyanate composed of 4,4'-methylene-bis(cyclohexyl isocyanate) or isophorone diisocyanate, and a polyhydroxy compound are blended so that their reaction molar ratio (NCO / OH) is 2.5 to 4.0, and an isocyanate-terminated prepolymer which is an intermediate product having an NCO content of 7.0 to 14.0% obtained by a polyurethane-forming reaction of this blend, and an aromatic polyamine which is a mixture of dimethylthiotoluenediamine or diethyltoluenediamine or both are blended at a reaction molar ratio (NCO / NH2) = 1.10 to 0.90, and a method of manufacturing in a step of casting and molding a liquid mixture of this blend can be adopted.

Effect of the Invention

[0025] In this invention, since a two-component urethane molding material is constituted of a main agent containing an isocyanate-terminated prepolymer which is an intermediate product of a polyurethane-forming reaction of an alicyclic diisocyanate and a polyhydroxy compound, and a curing agent containing an aromatic diamine which is liquid at room temperature and is a mixture of dimethylthiotoluenediamine or diethyltoluenediamine or both, the optical urethane lens has an advantage that there is no yellowing or browning due to thermal deterioration of the curing agent, and the transparency is high and stable even after molding and curing.

[0026] Furthermore, since the two-component urethane molding material for optical lenses of this invention can be cast at the lowest possible temperature, even when molded into polarized lenses equipped with a polarizing film, lenses that are susceptible to coloration and have high transmittance, or lenses with vivid colors, the transparency and color of these lenses do not change even after mixing, molding, and curing processes, resulting in optical lenses of stable quality.

[0027] Furthermore, by casting the two-component urethane molding material for optical lenses according to this invention, optical urethane lenses possessing the above advantages can be efficiently manufactured. [Brief explanation of the drawing]

[0028] [Figure 1] Chart showing the spectral transmittance of transparent eyeglass lens A in Examples 1 and 2, and Reference Examples 1 and 2. [Figure 2] Chart showing the spectral transmittance of transparent eyeglass lens A in Comparative Examples 1-3. [Figure 3] Examples 1 and 2, Reference Examples 1 and 2: Charts showing the spectral transmittance of eyeglass lens B. [Figure 4] Chart showing the spectral transmittance of eyeglass lens B in Comparative Examples 1-3 [Figure 5] Chart showing the spectral transmittance of eyeglass lens C in Example 1, Reference Example 1, and Comparative Example 3. [Modes for carrying out the invention]

[0029] An embodiment of this invention, a two-component urethane molding material for optical lenses, comprises a main component containing an isocyanate-terminated prepolymer, which is an intermediate product of the polyurethane formation reaction between an alicyclic diisocyanate and a polyhydroxy compound, and a curing agent containing an aromatic diamine, which is liquid at room temperature, and is dimethylthiotoluenediamine or diethyltoluenediamine or a mixture thereof.

[0030] Typical examples of optical lenses made of polyurethane resin, which are cast from a two-component urethane molding material, include eyeglass lenses such as clear lenses, sunglasses lenses, or polarized lenses.

[0031] The alicyclic diisocyanate used in this invention is preferably one or more aliphatic cyclic polyisocyanates selected from the group consisting of 4,4'-methylene-bis(cyclohexyl isocyanate) or isophorone diisocyanate, 2,5(6)-diisocyanatemethyl-bicyclo[2,2,1]heptane, and bis(isocyanatemethyl)cyclohexane.

[0032] Furthermore, with diisocyanates other than those exemplified above, it becomes difficult to obtain the desirable properties intended in this invention. For example, using hexamethylene diisocyanate, trimethylhexamethylene diisocyanate, hydrogenated XDl, norbornane diisocyanate, etc., makes it difficult to sufficiently extend the pot life of the resulting urethane resin.

[0033] The polyhydroxy compounds used in this invention are polyetherdiols or polyesterdiols with an average molecular weight of 700 to 1200, and mixtures thereof. As the polyetherdiol, polyoxytetramethylene glycol obtained by ring-opening polymerization of tetrahydrofuran and other polyetherdiols can be used. As the polyesterdiol, various known polyesters can be used, but 1,4-butanediol adipate and 1,6-hexanediol adipate are preferred.

[0034] The viscosity of the prepolymer obtained by reaction with diisocyanate is lower when the prepolymer is derived from polyetherdiol, which is advantageous for casting operations. Therefore, polyetherdiol is particularly preferred as the polyhydroxy compound used in this invention.

[0035] Furthermore, aliphatic polyols with a molecular weight of 300 or less may be used in combination to improve hardness and chemical resistance. Examples of aliphatic polyols include diols such as ethylene glycol, diethylene glycol, propylene glycol, and 1,4-butanediol, and triols such as trimethylolethane and trimethylolpropane.

[0036] In this invention, when producing a prepolymer obtained by reacting a polyisocyanate with a polyhydroxy compound, the reaction molar ratio (NCO / OH) is 2.5 to 4.0, and the NCO content of the resulting prepolymer is 7.0 to 14.0%. If the reaction molar ratio and NCO content are smaller than this range, the viscosity of the prepolymer becomes too high, making casting difficult, and the hardness also decreases. Conversely, if they are larger than the above range, the cured physical properties deteriorate, which is undesirable.

[0037] Among the aromatic diamines used in this invention, dimethylthiotoluenediamine (DMTDA) is represented by the following formula 1, is a liquid with a melting point of 4°C and low viscosity at room temperature (690 cps at 20°C), and may be an isomer mixture containing 3,5-dimethylthio-2,4-toluenediamine (2,4 isomer) and 3,5-dimethylthio-2,6-toluenediamine (2,6 isomer).

[0038] [ka]

[0039] Furthermore, commercially available DMTDA (liquid diamine curing chain extender) may contain 95% or more DMTDA, along with 4% or less methylthiotoluenediamine and 1% or less trimethylthiotoluenediamine. As a commercially available DMTDA product, "EtaCure 300," sold by Mitsui Chemicals Fine Co., Ltd. and others, can be used.

[0040] Among the aromatic diamines contained in the curing agent used in this invention, diethyltoluenediamine (DETDA) is a well-known chemical substance used as a chain extender for polyurethane elastomers. Its chemical structure is obtained by substituting the methylthio group with an ethyl group in dimethylthiotoluenediamine (DMTDA), as shown in Formula 1. A commercially available polyurethane chain extender that mainly contains this substance is EtaCure 100 Plus, which is sold by Albemarle and others.

[0041] In this invention, DETDA or DMTDA can be used individually as curing agents, but it is preferable to use an aromatic diamine mixed with both in combination to facilitate adjustment of the pot life.

[0042] The blending ratio of such curing agent is preferably 4 to 37 parts by mass per 100 parts by mass of the isocyanate-terminated prepolymer, in order to enable the lens to be molded with a pot life that allows for good workability, as described above. A more preferable blending ratio of curing agent is 5 to 30 parts by mass, and even more preferably 10 to 25 parts by mass.

[0043] Furthermore, by mixing 15 to 25 parts by mass of DMTDA and 1 to 10 parts by mass of DETDA with 100 parts by mass of the isocyanate-terminated prepolymer, the pot life time and color tone can be adjusted by using the resulting aromatic diamine and adjusting the mixing ratio within the aforementioned numerical range.

[0044] Since DETDA has a higher reactivity to isocyanate-terminated prepolymers than DMTDA, increasing the amount of DETDA used shortens the pot life, which in turn speeds up the curing time and improves productivity.

[0045] When the amount of DETDA added exceeds 10 parts by mass, the pot life is shortened and workability is significantly reduced, which is undesirable. For this reason, a more preferable amount of DETDA is 1 to 7 parts by mass, even more preferably 4 to 6 parts by mass, and the optimal amount is considered to be 5 parts by mass. Furthermore, adding DETDA at a concentration of 10% or less of DMTDA or other amines improves the color tone.

[0046] Furthermore, the molar ratio (NCO / NH2) of the prepolymer and aromatic polyamine in this invention is 1.10 to 0.90. The processing conditions for casting by mixing and heating, and the subsequent curing, can be those of known processing conditions or lower temperatures. In other words, because the predetermined curing agent used in this invention is liquid at room temperature, the mixture can be processed under relatively low mixing conditions of 100°C or below, reducing viscosity differences and enabling uniform mixing, and further allowing it to be used for casting.

[0047] To manufacture impact-resistant optical lenses for use as clear lenses such as eyeglass lenses, sunglasses lenses, or polarized lenses by casting the above-mentioned polyurethane resin material composition for casting, a well-known casting method can be employed.

[0048] In other words, the casting method involves providing a mold component in which a concave mold and a convex mold are fitted together in a liquid-tight manner via a gasket to form the lens, and then injecting a monomer into the cavity of this mold component for polymerization and curing.

[0049] In particular, when manufacturing optical lenses with polarizing properties, a polarizing element (polarizing film) is pre-set inside a ring-shaped gasket when fitting a concave and convex molded member together. Then, polymerization and curing can be performed by so-called insert molding, in which monomers of resin raw material are injected through injection holes formed in the molded member or gasket so that the polarizing element is covered with resin along both sides. [Examples]

[0050] [Examples 1 and 2, Reference Examples 1 and 2] <Prepolymer Manufacturing> 200 parts by mass of polytetramethylene ether glycol (PTG1000, manufactured by Hodogaya Chemical Co., Ltd., average molecular weight (MW) 1000) and 4 parts by mass of trimethylolpropane (TMP) were blended as polyol components. The mixture was heated while stirring in a nitrogen atmosphere and dehydrated at 100°C under reduced pressure of 5-10 mmHg for 1 hour. After dehydration, it was cooled and the isocyanate component H was removed at 80°C. 12 224 parts by mass of 4,4'-methylenebiscyclohexyl isocyanate (Sumitomo Bayer Urethane Co., Ltd.: Desmodulo W) was added as MDI, and the mixture was reacted at 100-110°C for 8 hours to produce an isocyanate-terminated prepolymer. The reaction molar ratio (NCO / OH) at this time was 3.5.

[0051] <Manufacturing of transparent lens A> (mixing with hardener and casting) The prepolymer manufactured as described above was degassed under reduced pressure at 80°C, and then, dimethylthiotoluenediamine [DMTDA(1), DMTDA(2)] or diethyltoluenediamine (DETDA), or both, were added as curing agents in the proportions (parts by mass) shown in Table 1, per 100 parts by mass of the prepolymer. Using the two-component urethane molding materials of Examples 1 and 2, and Reference Examples 1 and 2, each was mixed for 1 minute in a mixing and degassing machine, then heated to 95-100°C and poured into preheated glass molds for casting. The mixture was then cured at 95-100°C for 20 hours. The reaction molar ratio (NCO / NH2) at this time was 1.0. After curing, the mixture was cooled, and the transparent eyeglass lens A molded from the mold was released.

[0052] <Manufacturing of polarized lens B> In the mixing and casting process with the hardening agent described above, a gasket with a polarizing film set in the center was sandwiched between two molds, and the casting mixture of the two-component urethane molding material was injected between the polarizing film and the glass mold. Except for these differences, lens B was manufactured in the same manner as described above, having a gray tone with minimal color error and polarizing properties that allow for reliable identification of object colors without misinterpretation, just as when viewed with the naked eye.

[0053] The above polarizing film was produced by uniaxially stretching a 75 μm thick polyvinyl alcohol film four times, then immersing it in an aqueous solution (dye solution) containing 0.1 wt% iodine, 0.04 wt% direct fast orange and 0.02 wt% serious scarlet B direct dyes, and 0.01 wt% reactive dyes Mikalon yellow RS and 0.012 wt% Diamira red B. After that, it was immersed in an aqueous solution containing 3 wt% boric acid, drained, and then heat-treated at 70°C for 5 minutes to produce a 30 μm thick polarizing film. This polarizing film was pressed against spherical glass to form a sphere, and urethane adhesive was applied to both sides and dried. The resulting film was then set in the center of the gasket as described above.

[0054] <Manufacturing of polarized lens C> Lens C, which also has polarizing properties, was manufactured in the same manner as Lens B, except that the dyeing solution for the polarizing film was changed to a grayish color and the transmittance was increased to 72% or more, thereby creating a polarized eyeglass lens that can be used for driving at night.

[0055] [Comparative Example 1] In Reference Example 1, a two-component urethane molding mixture was prepared in the same manner as above, except that 37 parts by mass of 4,4'-methylenebis(2-chloroaniline) [MOCA (colorless crystal, melting point 110°C), also known as white moca] was used as the curing agent instead of dimethylthiotoluenediamine [DMTDA(1), DMTDA(2)] or diethyltoluenediamine (DETDA), and the curing reaction was carried out at 120°C. Using this mixture, a transparent lens A, a polarizing lens B, and a polarizing lens C for eyeglasses were manufactured.

[0056] [Comparative Example 2] In Reference Example 1, 40 parts by mass of 3,3'-dichloro-4,4'-diaminodiphenylmethane [MBOCA] (Cuamine® MT, melting point over 98°C) was used instead of dimethylthiotoluenediamine [DMTDA(1), DMTDA(2)] or diethyltoluenediamine (DETDA) as the curing agent. The mixture was heated to 100-110°C above its melting point, mixed, and cured. In addition, a two-component urethane molding mixture was prepared in the same manner, and a transparent lens A, a polarizing lens B, and a polarizing lens C for eyeglasses were manufactured using this mixture.

[0057] [Comparative Example 3] In Reference Example 1, a two-component urethane molding mixture was prepared in the same manner as above, except that 37 parts by mass of trimethylenebis(4-aminobenzoate)(CUA-4) was used instead of dimethylthiotoluenediamine [DMTDA(1), DMTDA(2)] or diethyltoluenediamine (DETDA) as the curing agent. This mixture was then used to manufacture clear lens A, polarized lens B, and polarized lens C for eyeglasses.

[0058] For the obtained transparent lens A and polarized lenses B and C for eyeglasses, the color coordinate values ​​L, a, and b in the UCS color space were measured using a device combining a Σ90 color measuring system and a Z-II optical sensor manufactured by Nippon Denshoku Industries Co., Ltd. Additionally, the spectral transmittance in the wavelength range including 410-750 nm was measured using a Hitachi U-2000 spectrophotometer. These results are shown in Table 1 and Figures 1-5.

[0059] Incidentally, the closer the color coordinate values ​​a and b are to 0, the less likely the color misperception will occur when used as an optical lens for eyeglasses, resulting in a gray color. A positive a value increases the reddish tone, while a negative a value increases the greenish tone. Similarly, a positive b value increases the yellowish tone, while a negative b value increases the blueish tone.

[0060] [Table 1]

[0061] As is clear from the results shown in Figure 1-5, the transmittance in the visible light range of the transparent lens A and polarizing lens B made from the molded materials of Examples 1 and 2 and Reference Examples 1 and 2 was about the same as that of the aforementioned lenses made from the molded material of Comparative Example 1, which used MOCA as a curing agent.

[0062] Furthermore, the transmittance in the visible light range of the transparent lens A and polarizing lenses B and C made from the molded materials of Examples 1 and 2 and Reference Examples 1 and 2 was higher than that of Comparative Examples 2 and 3. In particular, in the short wavelength range of 400 to 600 nm, the transmittance of Examples 1 and 2 and Reference Examples 1 and 2 was considerably higher than that of Comparative Examples 2 and 3.

[0063] Table 1 shows the color tones (color coordinate values ​​a, b) of each lens. Transparent lens A, polarized lenses B, and C obtained from the molded material of Comparative Example 1 showed a yellowish coloration with color coordinate values ​​b of 6.25, 2.95, and 5.67, respectively. However, the lenses using the molded materials of Examples 1 and 2, and Reference Examples 1 and 2, all had b values ​​lower than the aforementioned b values, indicating that yellowing was suppressed.

[0064] Furthermore, the MOCA (white moca) used in the molding material of Comparative Example 1 required heating to over 120°C during molding, and tended to undergo thermal degradation and produce brown foreign matter when heated for longer than the required time in dead points where the material accumulates during heating.

[0065] Furthermore, the transparent lens A and polarizing lens B made from the molded material of Comparative Example 2 had higher a and b values ​​than the same coordinate values ​​in Comparative Example 1, making it difficult to adjust these coordinate values ​​closer to 0 to achieve the desired gray color. The MOCA-like MT [MBOCA: Quamine® MT] used as a curing agent in the molded material of Comparative Example 2 mainly consists of compounds containing chlorine atoms, and therefore was not suitable for ensuring the safety of the work environment.

[0066] Furthermore, the color tone of transparent lens A, which was obtained from Comparative Example 3 using MOCA-like CUA-4 [trimethylenebis(4-aminobenzoate)(CUA-4)] as a curing agent, showed a considerably high b value (11.11), indicating yellowing.

[0067] The color tone observed in the molded material of Comparative Example 3 was similarly observed in both the gray polarized lens B, which is less prone to color misperception, and the gray polarized lens C, which has high visible light transmittance. In particular, polarized lens C showed a significantly higher b value than polarized lens B, and exhibited a considerably stronger yellow tint. Furthermore, the transparent lens A made from the molded material of Comparative Example 3 had poor release properties from the glass mold, and it was difficult to improve the manufacturing efficiency of the optical lens.

[0068] In contrast, Examples 1 and 2, and Reference Examples 1 and 2, which used DMTDA, DETDA, or a mixture of both as curing agents, could be mixed at a lower temperature than Comparative Example 1 for all of the transparent lens A and polarizing lenses B and C, and casting and curing treatment were possible at low temperatures of 100°C or below.

[0069] Furthermore, compared to the b values ​​of Reference Examples 1 and 2, which used either DMTDA or DETDA alone, Example 2, which used a mixture of DMTDA and DETDA, showed lower b values ​​and less yellowing in all lenses. Also, even with lenses of almost the same transmittance, lenses with less yellowing appeared to have better transparency.

[0070] The transparent lens A, the polarized lens B, and the polarized lens C, which are susceptible to coloration and have high transmittance, produced using the molded materials of Examples 1 and 2 and Reference Examples 1 and 2, all had lower a and b values ​​(indicating color tone) than those of Comparative Examples 2 and 3. Furthermore, Examples 1 and 2 and Reference Examples 1 and 2 exhibited excellent manufacturing efficiency due to their good release properties.

[0071] As described above, the optical lenses using the two-component urethane molding material of Examples 1 and 2, and Reference Examples 1 and 2, whether transparent lenses or polarizing lenses containing pigments, did not change in color tone before and after heat treatment, and there was no yellowing or browning due to thermal degradation of the curing agent, resulting in stable and excellent quality.

Claims

1. A method for producing polarized eyeglass lenses made of polyurethane resin with a visible light transmittance of 30 to 90%, comprising mixing a two-component urethane molding material at 100°C or less, the two-component urethane molding material being composed of a liquid base material containing an isocyanate-terminated prepolymer, which is an intermediate product of a polyurethane-forming reaction between an alicyclic diisocyanate and a polyhydroxy compound, and a curing agent containing 1 to 7 parts by mass of diethyltoluenediamine, an aromatic diamine that is liquid at room temperature, per 100 parts by mass of the isocyanate-terminated prepolymer, and then insert-molding the mixture to cover both sides of a polarizing film, followed by polymerization and curing.

2. 2. The method for producing a polarized eyeglass lens made of a polyurethane resin according to claim 1, wherein the alicyclic diisocyanate is 4,4'-methylene-bis(cyclohexyl isocyanate) or isophorone diisocyanate.

3. The method for producing a polarized eyeglass lens made of a polyurethane resin according to claim 1, wherein the curing agent is a curing agent containing a mixture of 15 to 25 parts by mass of dimethylthiotoluenediamine and 1 to 7 parts by mass of diethyltoluenediamine per 100 parts by mass of the isocyanate-terminated prepolymer.